Esensi Asrar al-Ahkam dalam Lirik Tembang Tombo Ati Gubahan Sunan Bonang sebagai Alternatif Obat Antidepresan - Syari’ah, Atiris; Rifqi, Naflah; Aimmah, Tania Nafida (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
Nowadays, depression is a type of psychiatric disorder that is most often experienced by people. Some people with symptoms of depression choose to go to a psychologist/psychiatrist to undergo treatment with prescription ‘anti-depressant drugs’ where all these chemicals have side effects on the patient’s health. In this case, Islam provides an alternative to these anti-depressants by practicing the essence of ‘Tombo Ati’ song by Sunan Bonang. This study uses the Asrarul Ahkam as a branch of science. That is proof that each of these Islamic syari’ah exists to safeguard religion, mind, soul, lineage (heredity) and protect property. In other words, the dimension of Islamic law is not limited to spiritualism/metaphysics. However, Islamic shari’ah can cover material dimensions, science and other worldly matters. This study aims to break the behavioral dichotomy between science and spiritual values in psychiatric treatment, especially depressive disorders in patients using the essence of Asrarul Ahkam in the song ‘Tombo Ati’ which contains, among other things: Medicine for the heart, there are 5 cases, reading the Qur'an and its meaning, night prayers, zikr at night, gathering with righteous people and fasting orders. This study uses a qualitative descriptive method and library research techniques to collect data. The results of the study show that some Sufistic psychotherapists who practice this have achieved effective results in reducing depression, stress and other mental disorders so that the essence of ‘Tombo Ati’ song is worthy of being an alternative option so that depressed patients are not addicted to anti-depressants.